Initial surgical and clinical experience with the Nucleus CI532 slim modiolar electrode in the UK. (4th July 2019) - Gomez Serrano, Manuel; Patel, Sharmila; Harris, Robert; Selvadurai, David
Abstract : Objective: The goal of this work is to describe the first experience in the UK with the slim pre-curved perimodiolar electrode Nucleus CI532 in a continuous series of patients in terms of surgical and clinical reliability and early performance outcomes. Method: In this retrospective review we describe the complication rate (including electrode array tip fold-over), NRT thresholds, hearing preservation, power efficiency and CI performance outcomes in a continuous series of 40 cochlear implants CI532 performed between October 2016 and November 2017 in 17 adults and 13 children with severe to profound hearing loss. Results: Preliminary data from these groups reveals some low-frequency hearing preservation in the CI532 group although none of the patients were conventional hearing preservation candidates. NRT thresholds, power efficiency, and BKB sentences in quiet were measured at 3 and 6 months post activation. There were no significant differences in these results. The average BKB score in quiet increases from 22% pre-operatively to 58% at 3 months and 70% at 6 months. In addition, although hearing preservation was not an objective, low-frequency thresholds were preserved in 20% of cases at 3 and 6 months post-operatively. Complications were observed in 5 cases, one case with non-device related aerocoele and four related to the device array: two cases of tip roll over, one case of the electrode array being placed extra-cochlea, and one case with the electrode buckling into the middle ear. The last 2 cases were dealt with per-operatively. Discussion: Our preliminary results with the CI532 implant indicate that it may be reliably placed with standard surgical techniques but care is needed during the deployment of the electrode. Further initial data suggest that switch on and early electrophysiological measures are comparable to the existing CI 512 device. However whilst preliminary, our data suggest that it may be possible to use this electrode for hearing preservation. However, further studies are required to determine its definitive advantage over other electrode designs. Conclusion: CI532 is a reliable device offering good initial results and could be an option for hearing preservation although further studies are required.